(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
This article presents detailed information on Afghanistan formal education system from 1868 to 2014. It provides information on Afghanistan’s vdevelopment of the modern education system from 1919 to 1929, a setback andthe revival of formal education from 1929 to 1973. It elaborates on the progress of formal education in the country from 1973 to 1978 and education losses from 1978 to 2001. In addition, it discusses the history of women’s formal education in the country and structural discrimination of girls’ and boys’ education in the history of Afghanistan. A timeline of the different regimes or governments and educational changes in Afghanistan can be seen at the end of this manuscript.